Vínculos locales y conexiones transnacionales del anticomunismo en Argentina y Uruguay en las décadas de 1950 y 1960 - Ernesto Bohoslavsky; Magdalena Broquetas (Nuevo mundo - Mundos Nuevos, 2017)
Scholar historiography has studied many aspects of Argentina and Uruguay political life in the fifties and sixties. However, it still remains under-examined the heterogeneous interests, alliances and conflicts within the wide rightist universe in those years. Argentina and Uruguay right-wing actors such as Liga Federal Ruralista (middle-class representants), neo-fascist bands and Anti-communist organizations were included in social and political transnational networks during the Cold War Era. In this paper are reconstructed some of those social and institutional links between Rio de la Plata’s Anti-communist organizations and with other inter-American and global networks, that allowed an intense circulation of ideas and persons. Particular attention is paid to the connections built by two main anti-communist actors: a “nationalist” current, identified by their authoritarian, catholic and Neo-fascist ideas, and violence-prone political style; and a “democratic” tendency, closer to US’ government point of view, pro-businessmen and allegedly committed with peaceful and formal political activities. The paper is based in different sources: commercial press, Anti-communist press and propaganda, Intelligence services reports and diplomatic information sent from Buenos Aires and Montevideo.